Review Paper on AI Desktop Voice - Verma, Jarvis Vipin (Journal of Advanced Research in Signal Processing and Applications, 2023)
The AI Assistant enables users to access online websites and calendar notification using natural language speaks through a PDA interface. The user must present the system and enabling the user to conduct a dialogue in which it is affable to operate between these domains. The JARVIS(SPA) is applied to an agent platform and includes a special PDA controller with plans for coordinating the accuse assistants and for encoding the system’s speak model. The agent-based dialogue model is at an upper level of abstraction, enabling the domain free plans in the dialogue model to be reused in alter JARVIS(SPA) systems.